Glucosyl hesperidin exhibits more potent anxiolytic activity than hesperidin accompanied by the attenuation of noradrenaline induction in a zebrafish model - Nishida, Takumi; Horita, Chihoko; Imagawa, Mikiya; Hibarino, Momoka; Tateno, Sayaka; Kubo, Yurina; Kawabe, Momoko; Morishita, Naoki; Endo, Shin; Shiozaki, Kazuhiro (Frontiers in Pharmacology, 2023)
Anxiety is a symptom of various mental disorders, including depression. Severe anxiety can significantly affect the quality of life. Hesperidin (Hes), a flavonoid found in the peel of citrus fruits, reportedly has various functional properties, one of which is its ability to relieve acute and chronic stress. However, Hes is insoluble in water, resulting in a low absorption rate in the body and low bioavailability. Glucosyl hesperidin (GHes) is produced by adding one glucose molecule to hesperidin. Its water solubility is significantly higher than that of Hes, which is expected to improve its absorption into the body and enhance its effects. However, its efficacy in alleviating anxiety has not yet been investigated. Therefore, in this study, the anxiolytic effects of GHes were examined in a zebrafish model of anxiety. Long-term administration of diets supplemented with GHes did not cause any toxicity in the zebrafish. In the novel tank test, zebrafish in the control condition exhibited an anxious behavior called freezing, which was significantly suppressed in GHes-fed zebrafish. In the black-white preference test, which also induces visual stress, GHes-fed zebrafish showed significantly increased swimming time in the white side area. Furthermore, in tactile (low water-level stress) and olfactory-mediated stress (alarm substance administration test) tests, GHes suppressed anxious behavior, and these effects were stronger than those of Hes. Increased noradrenaline levels in the brain generally cause freezing; however, in zebrafish treated with GHes, the amount of noradrenaline after stress was lower than that in the control group. Activation of c-fos/ERK/Th, which is upstream of the noradrenaline synthesis pathway, was also suppressed, while activation of the CREB/BDNF system, which is vital for neuroprotective effects, was significantly increased. These results indicate that GHes has a more potent anxiolytic effect than Hes in vivo, which may have potential applications in drug discovery and functional food development.